Auditoría de gestión de los procesos contables - administrativos con base en un sistema de gestión y planificación empresarial (sistema ERP) - Aguilar Sucasi, Alfonso Arturo (2007)
Currently, Ecuadorian paper industry has been forced to make changes in their products and how to make their processes in order to improve their productivity and better able to compete in a market where day decreases day involvement with the entry of new competitors both and abroad. Because of this incursion of new competitors in the market, most companies have begun to implement new management trends in your organization and benefit from them, and it is for this reason that the Ecuador Sancela Family Products Inc. has also seen the need to update and improve their processes. When performing an analysis of business situation, one can observe that has several internal advantages, as is mostly the experience of its professionals in each area or department that make up the different business processes.